PENGARUH KEPRIBADIAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA MAHASISWA MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS TADULAKO - Yusuf, Muh (Fakultas Ekonomi Universitas Tadulako, 2017)
The aim of this research is to determine simultaneous and partial influence of personality (X1) and family environment (X2) on entrepreneurial intentions (Y) of students. Subjects of this research involve students of The Management Department, Tadulako University with a sample of 88 respondents. This consists of 28 students of 2012 class, 26 students of 2013 class, and 34 students of 2014 class. Data collecting method apply observation, interviews, and questionnaires that analyzed with multiple linear regressions by using SPSS for Windows Release 16,0 software. The result shows that: 1) personality and family environment simultaneously have significant influence on entrepreneurial intention of student in the Management Department of University of Tadulako; 2) personality partially has significant influence on entrepreneurial intention of student in the Management Department of University of Tadulako; 3) family environment has significant influence on entrepreneurial intention of student in the Management Department of University of Tadulako.